Respuesta :
The correct answer is: [B]: " -4x + 2 " .
________________________________________
Explanation:
________________________________________
Method 1)
________________________________________
Given the equation for a line:
________________________________________
"y – 6 = –4(x + 1) " ; we are asked to choose
which equation (from the answer choices provided) the describes the same line (on a graph); or, in other words,
the same aforementioned equation,
which is "given" (in this very question being asked).
_______________________________________________
Note: All the FOUR (4) answer choices given are written in "slope-intercept form".
________________________________________________
We want to convert this equation to, and rewrite this equation in,
"slope-intercept form" ;
_________________________________
which is:
_________________________________
" y = mx + b " ;
in which:"y" is a single, "stand-alone" variable on the "left-hand side of the equation"; "m" is the coefficient of "x" ;
Furthermore, "m" is the slope of the line;
"b" is the "y-intercept"; or more precisely, the value of "x"
(that is; the "x-coordinate" of the point at which "y = 0" );
that is, the value of "x" ; or the "x-coordinate" of the point at which
the graph of the equation crosses the "x-axis".
_______________________________________________
So, given: "y – 6 = –4(x + 1) " ;
_______________________________________________
Let us start by expanding the "left-hand side of the equation" ;
__________________________________________________
that is: " - 4(x + 1) " ;
__________________________________________________
Note the "distributive property" of multiplication:
__________________________________________
a(b + c) = ab + ac ;a(b – c) = ab – ac .
_________________________________________________
→ So; -4(x + 1) = -4*x + (-4)*(1) = -4x + (-4) = -4x – 4 ;
→ Rewrite the equation:
________________________________________________
y – 6 = –4(x + 1) =
___________________________
→ y – 6 = -4x – 4 ;
___________________________
Add "6" to EACH SIDE of the equation; to isolate "y" on the "left-hand side" of the equation ; and to write the equation in "slope-intercept form" ;
__________________________________________________________
→ y – 6 + 6 = -4x – 4 + 6 ;
___________________________________
to get:
___________________________________
→ y = -4x + 2 ; which is: Answer choice: [B] .
___________________________________
Method 2).
___________________________________
The other formula for the equation of a line, given a particular point on that line;
" (x₁, y₁)" ; is: " y – y₁ = m(x – x₁) " ; in which "m" is the slope of that line.
So, in the original equation in the question:
____________________________________
" y – 6 = –4(x + 1) " ;
__________________________________
y₁ = 6
m = -4
x₁ = - 1 (note: This is a NEGATIVE value, because of the right-hand side of the equation in the formula is: "m(x – x₁)" ; is equal to: " –4(x + 1)" ;
So, we and to make "x₁" negative, because "x - (-1)" = "(x+1)" ; in order to make it a positive value in the original equation.
So we now that "m = -4" ; which is the case in all the answer choices.
On the right-hand side of our equation:
= -4(x +1) ; Use the distributive property:
-4(x + 1) = -4*x + -4(1) = -4x – 4 ;
y – 6 = -4x – 4 ;
Add "6" to both side of the equation; to isolate "y" on the left-hand side of the equation:
________________________________
y – 6 + 6 = -4x – 4 + 6 ;
________________________________
to get:
________________________________
y = -4x + 2 ; which is: Answer choice: [B] .
__________________________________________.
________________________________________
Explanation:
________________________________________
Method 1)
________________________________________
Given the equation for a line:
________________________________________
"y – 6 = –4(x + 1) " ; we are asked to choose
which equation (from the answer choices provided) the describes the same line (on a graph); or, in other words,
the same aforementioned equation,
which is "given" (in this very question being asked).
_______________________________________________
Note: All the FOUR (4) answer choices given are written in "slope-intercept form".
________________________________________________
We want to convert this equation to, and rewrite this equation in,
"slope-intercept form" ;
_________________________________
which is:
_________________________________
" y = mx + b " ;
in which:"y" is a single, "stand-alone" variable on the "left-hand side of the equation"; "m" is the coefficient of "x" ;
Furthermore, "m" is the slope of the line;
"b" is the "y-intercept"; or more precisely, the value of "x"
(that is; the "x-coordinate" of the point at which "y = 0" );
that is, the value of "x" ; or the "x-coordinate" of the point at which
the graph of the equation crosses the "x-axis".
_______________________________________________
So, given: "y – 6 = –4(x + 1) " ;
_______________________________________________
Let us start by expanding the "left-hand side of the equation" ;
__________________________________________________
that is: " - 4(x + 1) " ;
__________________________________________________
Note the "distributive property" of multiplication:
__________________________________________
a(b + c) = ab + ac ;a(b – c) = ab – ac .
_________________________________________________
→ So; -4(x + 1) = -4*x + (-4)*(1) = -4x + (-4) = -4x – 4 ;
→ Rewrite the equation:
________________________________________________
y – 6 = –4(x + 1) =
___________________________
→ y – 6 = -4x – 4 ;
___________________________
Add "6" to EACH SIDE of the equation; to isolate "y" on the "left-hand side" of the equation ; and to write the equation in "slope-intercept form" ;
__________________________________________________________
→ y – 6 + 6 = -4x – 4 + 6 ;
___________________________________
to get:
___________________________________
→ y = -4x + 2 ; which is: Answer choice: [B] .
___________________________________
Method 2).
___________________________________
The other formula for the equation of a line, given a particular point on that line;
" (x₁, y₁)" ; is: " y – y₁ = m(x – x₁) " ; in which "m" is the slope of that line.
So, in the original equation in the question:
____________________________________
" y – 6 = –4(x + 1) " ;
__________________________________
y₁ = 6
m = -4
x₁ = - 1 (note: This is a NEGATIVE value, because of the right-hand side of the equation in the formula is: "m(x – x₁)" ; is equal to: " –4(x + 1)" ;
So, we and to make "x₁" negative, because "x - (-1)" = "(x+1)" ; in order to make it a positive value in the original equation.
So we now that "m = -4" ; which is the case in all the answer choices.
On the right-hand side of our equation:
= -4(x +1) ; Use the distributive property:
-4(x + 1) = -4*x + -4(1) = -4x – 4 ;
y – 6 = -4x – 4 ;
Add "6" to both side of the equation; to isolate "y" on the left-hand side of the equation:
________________________________
y – 6 + 6 = -4x – 4 + 6 ;
________________________________
to get:
________________________________
y = -4x + 2 ; which is: Answer choice: [B] .
__________________________________________.